Evidence for anomalous water vapor sorption kinetics in cement based materials. (April 2015) - Saeidpour, Mahsa; Wadsö, Lars
Abstract: We used dynamic sorption balance measurements to evaluate the diffusivity for cement pastes with three different binders (OPC, OPC + 70% slag, OPC + 10% silica fume). The diffusion of water vapor in cement based materials is normally assumed to follow Fick's law of diffusion, but our results clearly show that Fick's law cannot completely describe the sorption process in our materials. In this paper we report the evidence for this anomalous sorption behavior and discuss a possible method to evaluate diffusivities from such measurements.